"Reverse brokering" and the consumption of accounting: A broker desk ethnography of an investment case. (August 2020) - Graaf, Johan; Johed, Gustav
Abstract: This study examines the under-researched equity sales function and analyses how equity brokers use accounting to generate individualized, contrarian investment recommendations to serve fund manager clients in a highly competitive market for investment advice. This study reports on the brokers' practices using an ethnographically inspired study of an equity sales desk and follows the lifecycle of a brokers' investment case referred to herein as "Indumine" (pseudonym). The analysis shows how the brokers used accounting to develop the case together with fund manager clients and against the analyst consensus – a practice the brokers referred to as "reverse brokering". Unlike previous analyses of how accounting influences investment decisions by being stable and objective, the brokers in our analysis continually added and abandoned accounting items in order to maintain a distance from consensus, remain subjective and interesting to clients, and achieve recognition. To make theoretical sense of such a use of accounting, this paper puts forth a consumption perspective of accounting. The argument is that the relevance of the accounting used for the brokers' investment recommendations is consumed when the information becomes factual and impersonal, and no longer sustains the brokers' contrarian view of the share; the challenge for the brokers is to sustain the economic potential of the case despite the temporary facticity of the accounting information. The paper proposes that this form of accounting consumption constitutes an elementary form of accounting use, operating in the shadow of more formal information infrastructure.